2019
DOI: 10.1177/1747954119861855
|View full text |Cite
|
Sign up to set email alerts
|

A cluster analysis of high-performance handball players' perceived motivational climate: Implications on motivation, implicit beliefs of ability and intention to be physically active

Abstract: The aims of this study were to uncover the different motivational climate profiles to compare differences on their implicit beliefs of sports ability, motivational orientation, and intention to be physically active, and finally to analyse the relationship of the gender with motivational climate profiles, in a large sample of high-performance handball players in Spain. A total of 444 (233 males, 211 females) high-performance handball players agreed to participate. They completed a questionnaire that included th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 54 publications
1
9
0
2
Order By: Relevance
“…In addition, it is observed that girls had higher values than boys in the variables of motivation and basic psychological needs satisfaction, such as autonomy, with a moderate effect, as similarly observed in the studies by Amado et al (2016) and Manzano-Sánchez et al (2019).. However, the results of the present study do not reflect significant differences in the IBPA between both genders, which is in contrast to the results obtained by Gómez-López et al (2019) in their study with a sample of handball players, in which they found significant differences in favour of girls. In this research, slightly higher values are found in boys, in line with the study by Munuera-Ortuño et al (2018) conducted with a sample of high school students, where the results reflect that boys have a greater IBPA than girls.…”
Section: Discussionsupporting
confidence: 55%
“…In addition, it is observed that girls had higher values than boys in the variables of motivation and basic psychological needs satisfaction, such as autonomy, with a moderate effect, as similarly observed in the studies by Amado et al (2016) and Manzano-Sánchez et al (2019).. However, the results of the present study do not reflect significant differences in the IBPA between both genders, which is in contrast to the results obtained by Gómez-López et al (2019) in their study with a sample of handball players, in which they found significant differences in favour of girls. In this research, slightly higher values are found in boys, in line with the study by Munuera-Ortuño et al (2018) conducted with a sample of high school students, where the results reflect that boys have a greater IBPA than girls.…”
Section: Discussionsupporting
confidence: 55%
“…On the other hand, the literature has shown that the players who trained in a competitive climate (ego climate) had higher levels of anxiety [46,47], lower satisfaction levels with sports practice [2,54], and a reduced intention to continue doing sport [14]. Previously, Ntoumanis and Biddle [45] found no significant direct link between motivational climate and competitive anxiety, thus implying that motivational climates could have an indirect impact on affective responses through the different goal orientations.…”
Section: Discussionmentioning
confidence: 99%
“…In a context of skill and achievement, in which athletes try to reach a goal and in which proving competence and ability is important [8], Roberts and Treasure [9] claim that physical and psychological well-being depends on the contexts where sports practice is carried out. More specifically, in the case of a team sport, such as handball, and at the height of adolescence, peers and coaches are the main social agents in a team [10,11] in terms of the motivational climate perceived during training [12][13][14][15][16]. As result of that self-evaluation cognitive process, and mediated for other psychological skills (e.g., perceived control or coping resources), it is not the perceived situations that directly cause the anxiety response, but certain situations of pressure or potential conflict that become stressful when they are assessed as threatening [17].…”
Section: Introductionmentioning
confidence: 99%
“…Although the satisfaction of basic psychological needs, experienced motivation or perceived performance are factors that determine adherence to sport, there are other variables such as enjoyment [ 66 ], implicit beliefs in their ability [ 67 ], and family or social support [ 68 , 69 ] that also determine the intention to continue practicing sport, so they should be considered jointly in future studies.…”
Section: Discussionmentioning
confidence: 99%